Implications of digital transformation related industry evolution on the strategy of Walmart, as an example of a U.S. grocery retailer - Sabisch, Sebastian Franz (2019)
The thesis studies the evolution of the grocery retail industry in the United States and its impact on the strategy of established firms in that industry. It builds upon a set of strategic concepts and frameworks, most importantly, the resource-based perspective and product-market position view on competitive advantage, and the theory on trajectories of industry evolution. Intensifying competition, technology innovation, and changing customer behavior are identified as the major trends in U.S. grocery retailing and the industry is found to be on an intermediating change trajectory. On the example of Walmart, the thesis examines implications of the industry evolution on the strategy of an incumbent and analyses the firm’s reaction to the changes in its environment during the past five years. The thesis concludes with a future outlook for incumbents on how to embrace these changes. Besides general valid recommendations, the thesis also suggests specific advice for Walmart, most importantly to lever its large network of retail locations.